2012
DOI: 10.1210/en.2011-2046
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Origin of the Structure and Function of Gonadotropin-Inhibitory Hormone: Insights from Lampreys

Abstract: Gonadotropin (GTH)-inhibitory hormone (GnIH) is a novel hypothalamic neuropeptide that inhibits GTH secretion in mammals and birds by acting on gonadotropes and GnRH neurons within the hypothalamic-pituitary-gonadal axis. GnIH and its orthologs that have an LPXRFamide (X = L or Q) motif at the C terminus (LPXRFamide peptides) have been identified in representative species of gnathostomes. However, the identity of an LPXRFamide peptide had yet to be identified in agnathans, the most ancient lineage of vertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 57 publications
0
107
0
Order By: Relevance
“…Analysis of the phylogenetic distribution of GnIH-type neuropeptides has revealed that they occur throughout the vertebrates, from primitive agnathan vertebrates through bony fish and amphibians to reptiles, birds, and mammals (25, 26). A comprehensive survey of the properties and functions of GnIH-type neuropeptides in each of the vertebrate classes is beyond the scope of this review and has been discussed elsewhere.…”
Section: From Lplrfamide To Gnih: the Bird Brain’s Contribution To Rfmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the phylogenetic distribution of GnIH-type neuropeptides has revealed that they occur throughout the vertebrates, from primitive agnathan vertebrates through bony fish and amphibians to reptiles, birds, and mammals (25, 26). A comprehensive survey of the properties and functions of GnIH-type neuropeptides in each of the vertebrate classes is beyond the scope of this review and has been discussed elsewhere.…”
Section: From Lplrfamide To Gnih: the Bird Brain’s Contribution To Rfmentioning
confidence: 99%
“…Therefore, we will focus here on studies in the most primitive extant vertebrates, the agnathans (lamprey, hagfish). A cDNA encoding a precursor of two GnIH-type peptides has been identified in the sea lamprey Petromyzon marinus , with expression revealed in the hypothalamus and gonads (26). Interestingly, injection of the GnIH-type peptides stimulates expression of GnRH and gonadotropins in lamprey, which contrasts with the inhibitory effects of GnIH in birds and mammals.…”
Section: From Lplrfamide To Gnih: the Bird Brain’s Contribution To Rfmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of their receptors also showed high sequence similarity. In addition, synteny analyses showed that GnIH gene and NPFF gene are both located near the HOX clusters [23], [24]. Because the HOX clusters are considered to have duplicated from a common ancestral gene during whole-genome duplication events through vertebrate evolution [25], GnIH gene and NPFF gene may also have diverged through whole-genome duplication in the course of evolution in vertebrates [23], [24].…”
Section: Introductionmentioning
confidence: 99%